Faktor-Faktor yang Mempengaruhi Pajak Pertambahan Nilai dan Pajak Penjualan Atas Barang Mewah Di Indonesia - Moraulina Marsella Simarmata (Universitas Negeri Medan, 2018)
PPN (Value-Added Tax) and PPnBM (Luxury Goods Sales Tax) are kind of taxesrecognized in Indonesia, and are classified into indirect tax which are imposed to the consumption in every level of production and distribution. As the taxes on consumption, PPN and PPnBM are highly dependent on the general economic condition. The indicators of macro economy may have influence on the revenues of PPN and PPnBM every year, and so is the amount of PKP (Taxable Entrepreneur) as PPN Collector according to the prevailing PPN Law. Therefore, the objective of the research was to find out how the amount of PKP, PDB, export value, import value, inflation, consumption expense, population and SBI interest rates influenced the revenues of PPN and PPnBM in Indonesia from 1986 until 2015. Ordinary Least Square method was applied for the analysis with multiple linear regression equation. The results showed that the amount of PKP, PDB, export value, import value, inflation, consumption expense, population and SBI interest rates simultaneously had a significant influence on the revenues of PPN and PPnBM in Indonesia. Partially, the amount of PKP, PDB, Export value, import value, consumption and population had positive influence on the revenues of PPN and PPnBM, whereas inflation and SBI interest rates had negative influence on the revenues of PPN and PPnBM in Indonesia.